Numerical modeling of railway track supporting system using finite-infinite and thin layer elements - Noorzaie, Jamaloddin; Thanoon, Waleed Abdulmalik; Yeat, W. F.; Moradipour, Parviz; Jaafar, Mohd Saleh (Materials and Energy Research Center, 2009)
The present contribution deals with the numerical modeling of railway track-supporting systems-using coupled finite-infinite elements-to represent the near and distant field stress distribution, and also employing a thin layer interface element to account for the interfacial behavior between sleepers and ballast. To simulate the relative debonding, slipping and crushing at the contact area between sleepers and ballast, a modified Mohr-Coulomb criterion was adopted. Further more an attempt was made to consider the elasto plastic materials’ non-linearity of the railway track supporting media by employing different constitutive models to represent steel, concrete and other supporting materials. It is seen that during an incremental-iterative mode of load application, the yielding initially started from the edge of the sleepers and then flowed vertically downwards and spread towards the center of the railway supporting system.